CRISPRscan: designing highly efficient sgRNAs for CRISPR/Cas9 targeting in vivo - Moreno-Mateos, Miguel A. (Nat Methods, 2015)
CRISPR/Cas9 technology provides a powerful system for genome engineering. However, variable activity across different single guide RNAs (sgRNAs) remains a significant limitation. We have analyzed the molecular features that influence sgRNA stability, activity and loading into Cas9 in vivo. We observe that guanine enrichment and adenine depletion increase sgRNA stability and activity, while loading, nucleosome positioning and Cas9 off-target binding are not major determinants. We additionally identified truncated and 5′ mismatch-containing sgRNAs as efficient alternatives to canonical sgRNAs. Based on these results, we created a predictive sgRNA-scoring algorithm (CRISPRscan.org) that effectively captures the sequence features affecting Cas9/sgRNA activity in vivo. Finally, we show that targeting Cas9 to the germ line using a Cas9-nanos-3′-UTR fusion can generate maternal-zygotic mutants, increase viability and reduce somatic mutations. Together, these results provide novel insights into the determinants that influence Cas9 activity and a framework to identify highly efficient sgRNAs for genome targeting in vivo.